2009
DOI: 10.1248/cpb.57.269
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Flowers. XXVI. Structures of Acylated Oleanane-Type Triterpene Oligoglycosides, Yuchasaponins A, B, C, and D, from the Flower Buds of <i>Camellia oleifera</i>&mdash;Gastroprotective, Aldose Reductase Inhibitory, and Radical Scavenging Effects&mdash;

Abstract: The methanolic extract and its 1-butanol-soluble fraction from the flower buds of Camellia oleifera ABEL were found to exhibit inhibitory effects on ethanol-and indomethacin-induced gastric mucosal lesions in rats. The ethyl acetate-and 1-butanol-soluble fractions also showed inhibitory effects on rat lens aldose reductase and scavenging effects on 1,1-diphenylpicryl-2-hydrazyl radical and superoxide. From the 1-butanol-soluble fraction, four new acylated oleanane-type triterpene oligoglycosides, yuchasaponins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…(Wang & Wei, 1990). Up to now, several flavonoids (Chen, Liau, Jong, & Chang, 2009;Du, Wu, & Chen, 2008;Luo, Li, & Xie, 2003;Wang, Jia, Zhu, Yang, & Zhou, 1986), lignans (Lee & Yen, 2006), tannins (Yoshida et al, 1994), and saponins (Sugimoto et al, 2009) were reported from the seeds, leaves, flower buds, seed cake, and seed oil. Our detailed chemical investigation on the seed cake of C. oleifera led to the isolation of two new kaempferol acetylated glycosides, together with six kaempferol derivatives and a simple phenolic compound.…”
Section: Introductionmentioning
confidence: 99%
“…(Wang & Wei, 1990). Up to now, several flavonoids (Chen, Liau, Jong, & Chang, 2009;Du, Wu, & Chen, 2008;Luo, Li, & Xie, 2003;Wang, Jia, Zhu, Yang, & Zhou, 1986), lignans (Lee & Yen, 2006), tannins (Yoshida et al, 1994), and saponins (Sugimoto et al, 2009) were reported from the seeds, leaves, flower buds, seed cake, and seed oil. Our detailed chemical investigation on the seed cake of C. oleifera led to the isolation of two new kaempferol acetylated glycosides, together with six kaempferol derivatives and a simple phenolic compound.…”
Section: Introductionmentioning
confidence: 99%
“…Long-range correlations were observed between the following proton and carbon pairs: H-1′ and C-3; H-1″ and C-2′; H-1‴ and C-3′; H-1″″ and C-2‴; H-21 and C-1″‴; H-22 and C-1‴‴. From all this evidence, the chemical structure of sanchakasaponin E was determined to be 21 8) together with angelic acid. The angelic acid was identified from retention time in a HPLC analysis of its p-nitrobenzyl ester.…”
mentioning
confidence: 90%
“…16 4 Hz, H 2 -28)] and four methines with an oxygen function [δ 3.14 (dd, J=3. 8 The positions of the acyl groups and the structure of the oligoglycoside moiety were confirmed based on double quantum filter correlation spectroscopy (DQF COSY) and heteronuclear multiple bond connectivity (HMBC) spectroscopy. Long-range correlations were observed between the following proton and carbon pairs: H-1′ and C-3; H-1″ and C-2′; H-1‴ and C-3′; H-1″″ and C-2‴; H-21 and C-1″‴; H-22 and C-1‴‴.…”
mentioning
confidence: 99%
“…As chemical constituents of this plant, saponins in the fruit and seeds, [2][3][4][5] flavonol glycosides in the leaves, 6) and triterpenes, 7) several hydrolyzable tannins, 8) acylated anthocyanins, 9) and purin alkaloids 10) in the flower have been reported. In the course of our studies on bioactive constituents of the flower buds of Camellia species, we have isolated triterpene saponins from C. sinensis L. (chakasaponins I-VI, floratheasaponins A-J), [11][12][13][14][15][16] C. oleifera ABEL (yuchasaponins A-D), 17) and C. sasanqua THUNB. (sasanquasaponins I-V).…”
mentioning
confidence: 99%
“…In the course of our studies on bioactive constituents of the flower buds of Camellia species, we have isolated triterpene saponins from C. sinensis L. (chakasaponins I-VI, floratheasaponins A-J), [11][12][13][14][15][16] C. oleifera ABEL (yuchasaponins A-D), 17) and C. sasanqua THUNB. (sasanquasaponins I-V).…”
mentioning
confidence: 99%